Parallel implementation of genomic sequences classification using modified gabor wavelet transform on multicore systems - Gunawan, Teddy Surya; Ambikairajah, Eliathamby (2012)
High processing time is required to classify genomic sequences and to identify protein coding of a DNA sequence. While computer performance has been driven largely by decreasing the size of chips while increasing the number of transistors they contain, the current computing trend is multicore system in which two or more independent cores are integrated into a single package. This paper presents the parallel implementation of the gene and exon identification of DNA sequences using the previously developed modified Gabor wavelet transform on multicore systems. Single Program Multiple Data (SPMD) parallel paradigm will be used in the parallel implementation. Furthermore, the efficiency of the proposed algorithm will be analyzed using Amdahl’s law.